The relationship between maxillary sinus retention cysts and nasal septum - Dağıstan, Hakan; Cengiz, Ceyhun; Haberal Can, İlknur (Journal of Surgery and Medicine, 2021)
Background/Aim: The etiology of re¬tention cysts of the maxillary sinuses (RCMs) and their relationship with the nasal septum is not fully elucidated. This study aimed to investigate the relationship between RCMs and the nasal septum. Methods: In this retrospective cohort study, computed tomography (CT) images of 208 patients who underwent paranasal sinus CT (PNsCT) imaging in our otolaryngology clinic in 2020 were scanned retrospectively. The demographic characteristics of the patients were accessed through the hospital’s electronic data recording system. The ages, genders, RCMs, and nasal septum statuses of all cases were noted. Results: RCM was significantly related to nasal septum deviation (NSD) to the right (P=0.001), while it was not related to NSD to the left (P=0.5). When the nasal septum was in the midline, the risk of developing RCMs was significantly reduced (P=0.007). The direction of septum deviation and the presence of RCMs were significantly related. Right NSD was an independent risk factor for the development of RCMs and increased the risk by 2.2-fold (P=0.002). Conclusion: RCMs, while thought to be asymptomatic and regress spontaneously, should be followed due to the possibility of transformation to antrochoanal polyp (ACP), and surgery should be considered, especially in symptomatic cases.